Conditional deletion of MAD2B in forebrain neurons enhances hippocampus-dependent learning and memory in mice - Cheng, Li; Su, Yanfang; Zhi, Kaining; Xie, Yaru; Zhang, Chun; Meng, Xianfang (Frontiers in Cellular Neuroscience, 2022)
Mitotic arrest deficient 2-like protein 2 (MAD2B) is not only a DNA damage repair agent but also a cell cycle regulator that is widely expressed in the hippocampus and the cerebral cortex. However, the functions of MAD2B in hippocampal and cerebral cortical neurons are poorly understood. In this study, we crossed MAD2Bflox/flox and calcium/calmodulin-dependent protein kinase II alpha (Camk2a)-Cre mice to conditionally knock out MAD2B in the forebrain pyramidal neurons by the Cre/loxP recombinase system. First, RNA sequencing suggested that the differentially expressed genes in the hippocampus and the cerebral cortex between the WT and the MAD2B cKO mice were related to learning and memory. Then, the results of behavioral tests, including the Morris water maze test, the novel object recognition test and the contextual fear conditioning experiment, suggested that the learning and memory abilities of the MAD2B cKO mice had improved. Moreover, conditional knockout of MAD2B increased the number of neurons without affecting the number of glial cells in the hippocampal CA1 and the cerebral cortex. At the same time, the number of doublecortin-positive (DCX+) cells was increased in the dentate gyrus (DG) of the MAD2B cKO mice. In addition, as shown by Golgi staining, the MAD2B cKO mice had more mushroom-like and long-like spines than the WT mice. Transmission electron microscopy (TEM) revealed that spine synapses increased and shaft synapses decreased in the CA1 of the MAD2B cKO mice. Taken together, our findings indicated that MAD2B plays an essential role in regulating learning and memory.